2020
DOI: 10.1111/fare.12435
|View full text |Cite
|
Sign up to set email alerts
|

Do Responsible Fatherhood Programs Work? A Comprehensive Meta‐Analytic Study

Abstract: Objective To investigate the effectiveness of fatherhood programs targeting unmarried, low‐income, nonresident fathers. Background Programs for unmarried, nonresident, and low‐income fathers increased in number and scope over the past decade. Programs for fathers have typically targeted five broad areas: positive father involvement, parenting, co‐parenting, employment, and child support payment. Method We conducted a systematic search for published and unpublished evaluations of fathering programs targeting un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…Although this and similar studies have been useful for gauging the perspectives of men in RFPs, less attention has been paid to how programs help men navigate these challenges and potentially promote more “gate opening” among mothers. We know that participation in RFPs is associated with improvements in coparenting skills, especially communication (Friend et al, ; Holmes et al, ), but we know less about other indirect ways that fatherhood programs support coparenting. This is crucial knowledge given how maternal gatekeeping is as much a response to fathers' behavior as it is a regulator of it (Cannon, Schoppe‐Sullivan, Mangelsdorf, Brown, & Sokolowski, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this and similar studies have been useful for gauging the perspectives of men in RFPs, less attention has been paid to how programs help men navigate these challenges and potentially promote more “gate opening” among mothers. We know that participation in RFPs is associated with improvements in coparenting skills, especially communication (Friend et al, ; Holmes et al, ), but we know less about other indirect ways that fatherhood programs support coparenting. This is crucial knowledge given how maternal gatekeeping is as much a response to fathers' behavior as it is a regulator of it (Cannon, Schoppe‐Sullivan, Mangelsdorf, Brown, & Sokolowski, ).…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that RFPs that serve fathers only through job services likely have positive, indirect benefits for coparenting. Even if RFPs do not significantly improve fathers' child support payments and economic and employment prospects (Holmes et al, ), they give marginalized men an opportunity to prove parenting commitments to mothers and others who use fathers' financial responsibility as evidence of dedication to family (Edin & Nelson, ). It also provides hope that coparenting relationships, even high‐conflict relationships, are still amenable to intervention even after fathers are no longer romantically linked with mothers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies are just beginning to be published. A recent meta‐analysis of 24 experimental and quasi‐experimental studies of fatherhood and coparenting programs for low‐income, unmarried, nonresident fathers revealed small but statistically significant positive effects for father involvement with children, parenting, and coparenting (Holmes, Hawkins, Egginton, Robbins, & Shafer, ). The strongest effect size was in coparenting skills.…”
Section: Significant Developmentsmentioning
confidence: 99%
“…As previously discussed, the U.S. federal government has invested considerable financial support for programs for low‐income nonresident fathers since 2005, yet only a small number of evaluations of these programs have been conducted to determine their effects. Holmes et al () concluded in their meta‐analysis that there is a continued need for evaluation of these fatherhood programs to determine their impact on fathers and families, best practices for addressing the needs of fathers, and ways to improve the capacity of programs to serve fathers.…”
Section: Persistent Challenges and Directions For Future Researchmentioning
confidence: 99%